2017
DOI: 10.1002/2016jc012542
|View full text |Cite
|
Sign up to set email alerts
|

Using a 1‐D model to reproduce the diurnal variability ofSST

Abstract: A wide range of applications, from air‐sea interaction studies to fisheries and biological modeling, need accurate, high resolution SST which requires that the diurnal signal is known; for many applications, diurnal estimates are necessary and should be included in blended SST products. A widely preferred approach to bridge the gap between in situ and remotely sensed measurements and obtain diurnal warming estimates at large spatial scales is modeling of the upper ocean temperature. This study uses the one‐dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…In incorporating wave breaking into the TKE equation he improved the models' ability to replicate the diurnal cycle. However, other studies have not found this necessary (e.g., Giglio et al, ; Karagali et al, ). Our results show that we are likely underpredicting the magnitude of diurnal warming and to include wave breaking effects would further reduce the diurnal magnitude.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In incorporating wave breaking into the TKE equation he improved the models' ability to replicate the diurnal cycle. However, other studies have not found this necessary (e.g., Giglio et al, ; Karagali et al, ). Our results show that we are likely underpredicting the magnitude of diurnal warming and to include wave breaking effects would further reduce the diurnal magnitude.…”
Section: Discussionmentioning
confidence: 89%
“…GOTM has previously been tailored for modeling diurnal variability (Pimentel et al, ), and this is the version of GOTM which we improve further for this current study. More recently, GOTM has also been used by Karagali et al () and Giglio et al () to successfully reproduce diurnal variability of SST at isolated sites with in situ moorings.…”
Section: Modelmentioning
confidence: 99%
“…Yet Karagali et al . [] show (for different sites) that a nine band solar absorption model performs better than the standard two band scheme in GOTM simulations of diurnal SST.…”
Section: Modelsmentioning
confidence: 99%
“…A number of numerical models are available to understand DV events and predict the variability of the DV process. They range from turbulence closure models (e.g., Karagali et al, 2017;Mellor & Yamada, 1982) to Geophysical Research Letters 10.1002/2017GL075008 statistical models (e.g., Gentemann et al, 2003;Price et al, 1987;Webster et al, 1996), to air-sea coupled models (e.g., Noh et al, 2011), and to physical-empirical hybrid models (e.g., Gentemann et al, 2009;Weihs & Bourassa, 2014). In essence, the balance between the net heat flux and wind-driven turbulent mixing over a daily cycle determines the magnitude of SST DV.…”
Section: A Simple DV Modelmentioning
confidence: 99%